SISTEM IE TERKAIT PEWARIS PADA KELUARGA TRADISIONAL JEPANG - Wedayanti, NP Luhur; Dewi, NMA Anita (Undiksha Press, 2021)
abstractTraditional Japanese society was a patrilineal society that had attitudes for men to preserve the family as a successor.Â The eldest son is always expected to be responsible for ancestor worship, wisely manage family inheritance to maintain the sustainability of the family. This system, Ie system, is a system that regulates all of the family members. Not only regarding how to behave toward family members but also the rules to choose the head of the family who will rule the whole of the family.Â